Multiple Genetic Alterations as Resistance Mechanism during Second-Line Lorlatinib for Advanced ALK-Rearranged Lung Adenocarcinoma: A Case Report - Annamaria Catino; Rosanna Lacalamita; Simona De Summa; Francesco Pesola; Stefania Tommasi; Domenico Galetta (Diagnostics, 2022)
Second and third-generation ALK-TKI inhibitors have showed better activity and have replaced crizotinib in most of cases of advanced ALK-rearranged lung adenocarcinoma. The emergence of resistance adversely affects also the activity of these newer drugs; in particular, lorlatinib often shows multiple and complex resistance mechanisms. The case reported here highlights the importance of reassessing the biomolecular profile during the disease course, both by tissutal and liquid biopsy, with the aim of improving the knowledge of these resistance mechanisms, and so identifying new drugs or sequences able to optimize the management of these patients.